The role of REST and HDAC2 in epigenetic dysregulation of Nav1.5 and nNav1.5 expression in breast cancer - Kamarulzaman, Nur Sabrina; Dewadas, Hemaniswarri Dewi; Chiuan, Yee Leow; Yaacob, Nik Soriani; Mokhtar, Noor Fatmawati (BioMed Central, 2017)
Background: Increased expression of voltage-gated sodium channels (VGSCs) have been implicated with strong metastatic potential of human breast cancer in vitro and in vivo where the main culprits are cardiac isoform Nav1.5 and its ‘neonatal’ splice variant, nNav1.5. Several factors have been associated with Nav1.5 and nNav1.5 gain of expression in breast cancer mainly hormones, and growth factors. Aim: This study aimed to investigate the role of epigenetics via transcription repressor, repressor element silencing transcription factor (REST) and histone deacetylases (HDACs) in enhancing Nav1.5 and nNav1.5 expression in human breast cancer by assessing the effect of HDAC inhibitor, trichostatin A (TSA). Methods: The less aggressive human breast cancer cell line, MCF-7 cells which lack Nav1.5 and nNav1.5 expression was treated with TSA at a concentration range 10–10,000 ng/ml for 24 h whilst the aggressive MDA-MB-231 cells was used as control. The effect of TSA on Nav1.5, nNav1.5, REST, HDAC1, HDAC2, HDAC3, MMP2 and N-cadherin gene expression level was analysed by real-time PCR. Cell growth (MTT assay) and metastatic behaviors (lateral motility and migration assays) were also measured. Results: mRNA expression level of Nav1.5 and nNav1.5 were initially very low in MCF-7 compared to MDA-MB-231 cells. Inversely, mRNA expression level of REST, HDAC1, HDAC2, and HDAC3 were all greater in MCF-7 compared to MDA-MB-231 cells. Treatment with TSA significantly increased the mRNA expression level of Nav1.5 and nNav1.5 in MCF-7 cells. On the contrary, TSA significantly reduced the mRNA expression level of REST and HDAC2 in this cell line. Remarkably, despite cell growth inhibition by TSA, motility and migration of MCF-7 cells were enhanced after TSA treatment, confirmed with the up-regulation of metastatic markers, MMP2 and N-cadherin. Conclusions: This study identified epigenetics as another factor that regulate the expression level of Nav1.5 and nNav1.5 in breast cancer where REST and HDAC2 play important role as epigenetic regulators that when lacking enhances the expression of Nav1.5 and nNav1.5 thus promotes motility and migration of breast cancer. Elucidation of the regulatory mechanisms for gain of Nav1.5 and nNav1.5 expression may be helpful for seeking effective strategies for the management of metastatic diseases.